2009
DOI: 10.1002/eji.200839116
|View full text |Cite
|
Sign up to set email alerts
|

A novel molecular interaction for the adhesion of follicular CD4 T cells to follicular DC

Abstract: Nectins and Nectin-like molecules (Necls) play a critical role in cell polarity within epithelia and in the nervous and reproductive systems. Recently, immune receptors specific for Nectins/Necls have been described. Since expression and distribution of Nectins/Necls is often subverted during tumorigenesis, it has been suggested that the immune system may use these receptors to recognize and eliminate tumors. Here we describe a novel immunoreceptor, WUCAM, which is expressed on human follicular B helper T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
237
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(245 citation statements)
references
References 34 publications
(64 reference statements)
6
237
1
1
Order By: Relevance
“…[10][11][12] TIGIT harbors one extracellular immunoglobulin domain, a type 1 transmembrane region, and an immunoglobulin tail tyrosine (ITT)-like phosphorylation motif followed by an ITIM (immunoreceptor tyrosine-based inhibition motif) of the cytoplasmic tail. 13 The physical ligands of TIGIT were identified as the poliovirus receptor (PVR, or CD155) and the PVRL2 (Nectin2, or CD112).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] TIGIT harbors one extracellular immunoglobulin domain, a type 1 transmembrane region, and an immunoglobulin tail tyrosine (ITT)-like phosphorylation motif followed by an ITIM (immunoreceptor tyrosine-based inhibition motif) of the cytoplasmic tail. 13 The physical ligands of TIGIT were identified as the poliovirus receptor (PVR, or CD155) and the PVRL2 (Nectin2, or CD112).…”
mentioning
confidence: 99%
“…13 The physical ligands of TIGIT were identified as the poliovirus receptor (PVR, or CD155) and the PVRL2 (Nectin2, or CD112). 10,12 TIGIT can bind to PVR of human dendritic cells to enhance interleukin 10 (IL-10) production, which inhibits T-cell activation. 10 Kuchroo et al 14 showed that TIGIT harbors a T-cell-intrinsic inhibitory function to suppress T-cell activation.…”
mentioning
confidence: 99%
“…24 Washington University cell adhesion molecule Washington University cell adhesion molecule (WUCAM) is another recently identified novel receptor for PVR/CD155. 26 WUCAM sequences aligned with nectin-1-4, PVR/CD155, CD226 and CD96 in the distal Ig-V-type domain, according to the National Center Biotechnology Information cDNA database. WUCAM has a single Ig-V-type domain, a transmembrane-spanning sequence and a short cytoplasmic tail.…”
Section: Tactile/cd96mentioning
confidence: 99%
“…Furthermore, the interaction between WUCAM on human follicular B helper T cells and PVR/CD155 on follicular dendritic cell (DC) within the germinal center mediates adhesion of T follicular helper cells to follicular DCs and might facilitate the generation of T-cell-dependent antibody responses. 26 …”
Section: Tactile/cd96mentioning
confidence: 99%
“…[11] exprimées à la surface de cellules adjacentes. Des membres de la famille des nectines et nectineslike sont aussi capables de former des interactions hétérophiliques en trans avec d'autres partenaires appartenant à la SFIg tels que DNAM1 (DNAX accessory molecule-1 ou CD226) [12], tactile (CD96) [13], CRTAM (Class I-restricted T cell-associated molecule) [14] et WUCAM (Washington University cell adhesion molecule) [15]. Ainsi, un réseau complexe de 17 trans-interactions hétérophiliques différentes avec les protéines nectines et nectines-like est actuellement décrit, certaines nectines étant associées à une fonction biologique (Figure 2).…”
Section: Les Protéines Nectines Et Nectines-like : Molécules D'adhéreunclassified